PSOCOPTERA AND WALLACE'S LINE: COLLECTIONS FROM THE ISLANDS OF BALl AND LOMBOK - Thornton, Ian W.B (Treubia, 2015)
Seventy-six species of Psocoptera are now known from the islands of Bali and Lombok which lie on either side of Wallace's line. They represent 31 genera in 15 families, and 40 are newly described. Sixty-five species are known from Bali, and 32 from Lomboh. The majority of Bali species were not found on Lombok, whereas the majority of Lombok species also occur on Bali. The Lombok fauna, thus appears to be a 'sample' of that of Bali. Over half the 21 species found on both islands are known from elsewhere, 5 of them being widespread. Only 4 species are known otherwise only from most easterly regions - 2 from Australia.